Prevalence, antibiotic resistance and virulence of Enterococcus spp. in Egyptian fresh raw milk cheese. (April 2015) - Hammad, Ahmed M.; Hassan, Hamdy A.; Shimamoto, Tadashi
Abstract: Little is known about the influx of multidrug and/or virulent enterococcal strains from fresh raw milk cheese to the human digestive tract. In this study, 100 samples of popular Egyptian raw milk cheese, karish cheese, were analyzed to determine the incidence of Enterococcus spp., especially Enterococcus faecalis and Enterococcus faecium . We recovered 120 enterococcal isolates from 90 (90%, 90/100) samples. Thirty-seven strains (30.8%, 37/120), were identified as E. faecium and 13 (10.8%, 13/120) as E. faecalis . Fourteen (11.6%, 14/120) strains carried antibiotic resistance genes. These included tet (M), tet (L), tet (K), erm (B), and aph (3′), which were detected in 5%, 3.3%, 0.83%, 0.83%, and 0.83% of isolates, respectively. Interestingly, resistance to the most recently introduced anti-Gram-positive agent, linezolid, was detected alone and in combination with vancomycin resistance in 6.6% and 2.5% of isolated strains, respectively. Additionally, eight strains of E. faecalis carried one or more virulence genes, including asa1, cylA, esp, gelE, and hyl, while only one E. faecium strain carried gelE . Tn 916 -like elements detected in 11 (9.3%, 11/120) enterococcal strains. In conclusion, the fresh raw milk cheese, karish cheese, is a potential reservoir of antibiotic resistant and virulent enterococci that may constitute a public health hazard. To the best of our knowledge, this study provides the first detailed analysis about the ecology of antibiotic resistance and virulence in a variety of enterococci isolated from fresh raw milk cheese in Africa that promoting the necessary criteria for the phenotypic and molecular analysis of enterococci in this type of cheese to ensure their safety. Highlights: We characterized 120 strains of enterococci isolated from 100 karish cheese samples. Several antibiotic resistance and virulence genes were detected. Karish cheese is a potential reservoir of antibiotic resistant and virulent enterococci.